Open complex distal femur intraarticular fracture with Hoffa extension, extensor mechanism tear and post-recovery secondary traumatic peri implant fracture: report on an uncommon chronology - Tomar, Lavindra; Govil, Gaurav; Dhawan, Pawan (International Journal of Research in Orthopaedics, 2020)
Complex distal femur fractures with Hoffa’s extension are uncommon. An associated open fracture with extensor mechanism disruption are rarely reported. A secondary post-traumatic post-recovery peri-implant fracture is a rare presentation. 28-year-old pilon rider male sustained open complex fracture of left metaphyseal distal femur with Hoffa extension and tear in extensor mechanism. He was treated within a golden hour period of wound management. Primary stabilization by distal femoral locking plate and cannulated cancellous screw was done along with primary bone grafting and repair of extensor mechanism. At sixteen weeks, clinic-radiological progression allowed him his pre-injury activities. At seven months, a second trauma resulted in a non-prosthetic peri-implant femoral fracture, another unusual occurrence. Re-osteosynthesis with grafting was done. At twenty months of the primary injury, there was good functional outcome with a painless range of knee flexion to 130° without any extensor lag. Open complex distal femur injury with an associated secondary hit peri-implant fracture presented with significant challenges in management of soft-tissue and reconstruction of bony defect. The early presentation within a golden hour period allowed an early injury assessment to implement primary biological fixation as a treatment modification. Aim was to achieve favorable functional outcome which allowed early return to pre-injury status.